3x3 Dimensional Special Matrices Associated with Fibonacci and Lucas Numbers - Sinan Karakaya; Tuğba Petik; Halim Özdemir (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In the study, it has been developed a method for deriving special matrices of 3x3 dimensions, whose powers are related to Fibonacci and Lucas numbers, and some special matrices have been found via the method developed. Also, it has been given some identities related to the matrices found.